How Cultural Diversity Drives Innovation: Surnames and Patents in US History - Posch, Max; Schulz, Jonathan; Henrich, Joseph (Journal of Political Economy, 2026)
This paper examines the impact of cultural diversity on innovation. Focusing on the United States from 1850 to 1940, we develop a novel surname-based measure of cultural diversity and combine this with patent data. Leveraging quasi-random variation in counties' surname compositions driven by historical immigration, we find that rising diversity increased both the quantity and quality of innovation within counties and for individual inventors. Examining mechanisms, we provide evidence suggesting that greater surname diversity accelerated innovation both by expanding the range of ideas, skills and perspectives available for recombination and by fostering the diverse social interactions that facilitate idea sharing.